An Analysis of the Effects of Independent Commissioners, Institutional Ownership, and Audit Committees on Stock Prices (An Empirical Study of Construction Companies Listed on the Indonesia Stock Exchange during the 2019–2022 Period) - Rio Ferdinand; Syarifah Zuhra; Dwila Maresti (The Future of Education Journal, 2026)
This study aims to analyze the influence of corporate governance mechanisms, proxied by Independent Commissioners, Institutional Ownership, and the Audit Committee, on Stock Prices in construction sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period. The sampling method employed a purposive sampling technique, resulting in 10 construction companies that met the criteria with a total of 40 data observations. The analysis method used is multiple linear regression analysis processed with the assistance of SPSS software. The research results partially (t-test) show that the Independent Commissioners, Institutional Ownership, and Audit Committee variables do not have a significant effect on Stock Prices. Furthermore, the simultaneous test results (F-test) also indicate that the three independent variables together do not significantly influence the Stock Price of construction sector companies. The Adjusted R Square value of 0.058 indicates that the variation in Stock Prices explained by this model is only 5.8%, while the remaining 94.2% is explained by other variables outside the research model. These findings imply that the implementation of corporate governance in the construction industry in Indonesia during the observation period tends to merely satisfy administrative compliance and regulatory formalities, and has not been able to provide a substantive impact on influencing investor assessments and decisions in the capital market.